2001
DOI: 10.1097/00129492-200109000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Tremor in Otosurgery: Influence of Physical Strain on Hand Steadiness

Abstract: The tremor data are interpreted as a recommendation to avoid physical exertion before microsurgery. In cases of absolute necessity for hand steadiness, two-handed manipulations are preferable. Further, hand steadiness might be improved by microsurgical training and experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 9 publications
1
42
0
2
Order By: Relevance
“…In line with others [Coulson et al, 2010;Murbe et al, 2001], we observed that the support of the free hand by the contralateral hand or as a two-point support has a significant effect on the maximum amplitude and the peak frequency of deviations.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with others [Coulson et al, 2010;Murbe et al, 2001], we observed that the support of the free hand by the contralateral hand or as a two-point support has a significant effect on the maximum amplitude and the peak frequency of deviations.…”
Section: Discussionsupporting
confidence: 92%
“…caused by tremor, unsteadiness of the hand or of the arm/elbow). This is well known and led to the recommendation to limit physical activities before surgery [Murbe et al, 2001].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed it seems that concerns of a decrement owing to tremor remain unfounded as tremor has been found to be very infrequent with caffeine use at lower levels, and more of a concern when much higher doses are used 30 . However, reaction time, which is a measure of alertness, did improve significantly with the administration of caffeine, and caffeine with taurine, compared with the placebo state.…”
Section: Discussionmentioning
confidence: 99%
“…Murbe et al examined hand tremor while performing a simulated microsurgical task using a force cell and a fine-needle while supporting the wrist. 7 The subjects were asked to push and hold a modeled stapes head into a specific position and maintain it in place. The hand was stabilized using a counterweight, which lead to much smaller tremor amplitudes (in the range of 10 lm).…”
Section: Discussionmentioning
confidence: 99%